Recognition of, and attitudes towards, people with depression and psychosis with/without alcohol and other drug problems: results from a national survey of Australian paramedics. Issue 12 (4th December 2018) - McCann, Terence V; Savic, Michael; Ferguson, Nyssa; Cheetham, Alison; Witt, Katrina; Emond, Kate; Bosley, Emma; Smith, Karen; Roberts, Louise; Lubman, Dan I
Abstract : Objective: Continuing stigma towards mental health problems means that many individuals—especially men—will first present in crisis, with emergency services often the first point of call. Given this situation, the aims of this paper were to assess paramedics' ability to recognise, and their attitudes towards, males with clinically defined depression and psychosis with and without comorbid alcohol and other drug (AOD) problems. Methods: A cross-sectional national online survey of 1230 paramedics throughout Australia. The survey was based on four vignettes: depression with suicidal thoughts, depression with suicidal thoughts and comorbid alcohol problems, and psychosis with and without comorbid AOD problems. Results: Just under half of respondents recognised depression, but this decreased markedly to one-fifth when comorbid AOD problems were added to the vignette. In contrast, almost 90% recognised psychosis, but this decreased to just under 60% when comorbid AOD problems were added. Respondents were more likely to hold stigmatising attitudes towards people in the vignettes with depression and psychosis when comorbid AOD problems were present. Respondents endorsed questionnaire items assessing perceived social stigma more strongly than personal stigma. Desire for social distance was greater in vignettes focusing on psychosis with and without comorbid AOD problems than depression with and without comorbid AOD problems. Conclusions: Paramedics need a well-crafted multicomponent response which involves cultural change within their organisations and more education to improve their recognition of, and attitudes towards, clients with mental health and AOD problems. Education should focus on the recognition and care of people with specific mental disorders rather than on mental disorders in general. It is essential that education also focuses on understanding and caring for people with AOD problems. Educational interventions should focus on aligning beliefs about public perceptions with personal beliefs about people with mental disorders and AOD problems.